Hyposalivation and 10‐year all‐cause mortality in an elderly Japanese population. (10th January 2018) - Iwasaki, Masanori; Borgnakke, Wenche S.; Yoshihara, Akihiro; Ito, Kayoko; Ogawa, Hiroshi; Nohno, Kaname; Sato, Misuzu; Minagawa, Kumiko; Ansai, Toshihiro; Miyazaki, Hideo
Abstract : Objective: To evaluate the association of salivary flow rate with all‐cause mortality among older Japanese adults. We hypothesised that hyposalivation would be a marker for mortality. Background: Hyposalivation, which is an objectively measurable decrease in salivary flow, is highly prevalent among older adults. It is associated with malnutrition and poor general health. Methods: The study population comprised 600 community‐dwelling Japanese adults (306 men and 294 women), who were 70 years old at baseline. They underwent stimulated salivary flow rate (SSFR) measurements and were followed up during a 10‐year study period. After stratification by sex, the hazard ratios of all‐cause mortality were estimated using Cox proportional hazards regression analysis comparing groups with and without hyposalivation (ie, SSFR < 0.7 mL/min). Results: The baseline prevalence of hyposalivation was 27.8% (85/306) among men and 47.3% (139/294) among women. During a mean (standard deviation) follow‐up period of 104 (27) months, 80 deaths occurred: 60 (75.0%) deaths among men and 20 (25.0%) deaths among women. After adjusting for the number of remaining teeth, smoking status, exercise, hypoalbuminemia, diabetes and cardiovascular disease, hyposalivation at baseline was significantly associated with all‐cause mortality among men (adjusted hazard ratio, 1.71; 95% confidence interval, 1.01‐2.89). In contrast, no association between SSFR and all‐cause mortality existed among women. Conclusion: Hyposalivation could be a marker for all‐cause mortality among older community‐dwelling Japanese men. Future studies investigating the association between SSFR and cause‐specific mortality are warranted.